Low availability of choline in utero disrupts development and function of the retina. Issue 8 (15th May 2019) - Trujillo‐Gonzalez, Isis; Friday, Walter B.; Munson, Carolyn A.; Bachleda, Amelia; Weiss, Ellen R.; Alam, Nazia M.; Sha, Wei; Zeisel, Steven H.; Surzenko, Natalia
ABSTRACT: Adequate supply of choline, an essential nutrient, is necessary to support proper brain development. Whether prenatal choline availability plays a role in development of the visual system is currently unknown. In this study, we addressed the role of in utero choline supply for the development and later function of the retina in a mouse model. We lowered choline availability in the maternal diet during pregnancy and assessed proliferative and differentiation properties of retinal progenitor cells (RPCs) in the developing prenatal retina, as well as visual function in adult offspring. We report that low choline availability during retinogenesis leads to persistent retinal cytoarchitectural defects, ranging from focal lesions with displacement of retinal neurons into subretinal space to severe hypocellularity and ultrastructural defects in photoreceptor organization. We further show that low choline availability impairs timely differentiation of retinal neuronal cells, such that the densities of early‐born retinal ganglion cells, amacrine and horizontal cells, as well as cone photoreceptor precursors, are reduced in low choline embryonic d 17.5 retinas. Maintenance of higher proportions of RPCs that fail to exit the cell cycle underlies aberrant neuronal differentiation in low choline embryos. Increased RPC cell cycle length, and associated reduction in neurofibromin 2/Merlin protein, an upstream regulator of the Hippo signaling pathway, at least in part, explain aberrant neurogenesis in low choline retinas. Furthermore, we find that animals exposed to low choline diet in utero exhibit a significant degree of intraindividual variation in vision, characterized by marked functional discrepancy between the 2 eyes in individual animals. Together, our findings demonstrate, for the first time, that choline availability plays an essential role in the regulation of temporal progression of retinogenesis and provide evidence for the importance of adequate supply of choline for proper development of the visual system.—Trujillo‐Gonzalez, I., Friday, W. B., Munson, C. A., Bachleda, A., Weiss, E. R., Alam, N. M., Sha, W., Zeisel, S. H., Surzenko, N. Low availability of choline in utero disrupts development and function of the retina. FASEB J. 33, 9194–9209 (2019). www.fasebj.org